Investigation of the structure and mechanical properties of stainless steel alloyed with silver. Issue 1 (June 2021) - Kaplan, M A; Ivannikov, A Yu; Gorbenko, A D; Mikhailova, A V; Kirsankin, A A; Kalaida, T A; Konushkin, S V; Sevostyanov, M A
Abstract: The paper contains information of the development of technology for smelting stainless steel for application in the manufacture of medical devices. Smelting was carried out in electric arc vacuum furnaces. The technology has been developed for producing sheets with a thickness of 1 ÷ 1.25 mm for further research of mechanical properties. To study the structure, thin sections of the alloys were obtained by melting and further rolling. The mechanical properties of the samples and their structure have been studied. The results show that the addition of a small amount of silver decreases the mechanical properties of the steel. In the ingots, a dendritic structure is observed, and after warm rolling, the structure has a pronounced fine-grained austenitic structure.